Periodic Solution for Nonlinear System of Differential Equations Depending on The Gamma Distribution - Butris, Raad N. (Science Journal of University of Zakho, 2014)
In this paper we study the periodic solution of nonlinear system of differential equations depending on the gamma distribution by using the numerical analytic method to investigate periodic solutions of ordinary differential equation which given by Samoilenko A. M. .These investigations lead us to improving and extending this method. Also we expand the results gained by Samoilenko A. M. to change the periodic system of nonlinear differential equations to periodic system of nonlinear differential equations depending the on gamma distribution.